The Role and Teacher's Understanding in Implementing Curriculum on Vocational High School - Nurmalasari, Riana; Oktaviastuti, Blima; Nafiah, Annisau (Universitas Negeri Malang, 2019)
This study aims to describe the teacher's understanding and how teacher’s role in the implementation of the 2013 curriculum. This research uses a descriptive qualitative research design with case study. Research data supported by research tools in the form of audio-visual and field notes. The informants are the headmaster, the vice minister of curriculum, teachers, and students who carry out learning using the 2013 curriculum at SMK 1 Kertosono. Based on the results of the analysis, it is known that the understanding of teachers is not so fully understood the 2013 curriculum as a whole. The role of teacher for implementation of the 2013 curriculum conducted by teachers including: (1) Planning, teachers in making learning plans based on the results of teacher group discussions conducted between teacher peers and the internet; (2) Implementation, the implementation of learning conducted by the teacher includes three activities, namely the introduction, main, and closing activities; and (3) Assessments, assessments made by teachers are authentic assessments, which include; assessment of attitudes, knowledge and skills.